Form and Functional Repair of Long Bone Using 3D Printed Bioactive Scaffolds - Tovar, Nick; Witek, Lukasz; Atria, Pablo; Sobieraj, Michael; Bowers, Michelle; Lopez, Christopher; Cronstein, Bruce; Coelho, Paulo G (Journal of tissue engineering and regenerative medicine, 2018)
Injuries to the extremities often require resection of necrotic hard tissue. For large bone defects, autogenous bone grafting is ideal, but similar to all grafting procedures, is subject to limitations. Synthetic biomaterial driven engineered healing offers an alternative approach. This work focuses on three-dimensional (3D) printing technology of solid-free form fabrication (SFF), more specifically robocasting/direct write. The research hypothesizes that a bioactive calcium-phosphate scaffold may successfully regenerate extensive bony defects in vivo and that newly regenerated bone will demonstrate mechanical properties similar to native bone as healing time elapses. Robocasting technology was used in designing and printing customizable scaffolds, composed of 100% beta tri-calcium phosphate (β-TCP), which were used to repair critical sized long-bone defects. Following full thickness segmental defects (~11mm x full thickness) in the radial diaphysis in New Zealand White rabbits a custom 3D printed, 100% β-TCP, scaffold was implanted or left empty (negative control) and allowed to heal over 8, 12, and 24 weeks. Scaffolds and bone, en bloc, were subjected to micro-CT and histological analysis for quantification of bone and scaffold expressed as a function of percentage. Additionally, biomechanical testing at two different regions: i) bone in the scaffold (BiS) and ii) in native radial bone (control) was conducted to assess the newly regenerated bone for reduced elastic modulus (E ) and hardness (H) using nanoindentation. Histological analysis showed no signs of any adverse immune response while revealing progressive remodeling of bone within the scaffold along with gradual decrease in 3D-scaffold volume over time. MicroCT images indicated directional bone ingrowth, with an increase in bone formation over time. Reduced elastic modulus (E ) data for the newly regenerated bone presented statistically homogenous values analogous to native bone at the three-time points, while hardness (H) values were equivalent to the native radial bone at 24 weeks. The negative control samples showed limited healing at 8 weeks. Custom engineered β-TCP scaffolds are biocompatible, resorbable, and can directionally regenerate and remodel bone in a segmental long bone defect in a rabbit model. Custom designs and fabrication of β-TCP scaffolds for use in other bone defect models warrant further investigation.